Sistema de informação gerencial (SIG) na gestão de materiais e estoque no setor público - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The material management and stock management are essential parts of maintaining order and transparency regarding an organization's resources. In this sense, the implementation of a Management Information System (MIS) favors the efficiency of both. In view of the above, this article aims to investigate the contribution of the Management Information System (GIS) in the management of materials and stocks at the City Council of Sant’Ana do Livramento/RS. Specific objectives include the contextualization of materials management; the specification of inventory management and the analysis of the Management Information System (MIS) in materials management and inventory management. In methodological terms, a qualitative, descriptive research was adopted, using a case study as a collection method. For this, an interview script was prepared and applied to 3 (three) different sectors of the institution, totaling 12 (twelve) interviewees. Among the main results, the positive influence of GIS on materials and inventory management stands out. However, there was a lack of a completely integrated system. However, although there are improvements to be made, the implementation of the GIS proved to be satisfactory in the management of materials and stocks, providing benefits to the institution.
Management information system (MIS) in materials and stock management in the public sector
Keywords: Gestão de material; Setor público; Sistema de Informação Gerencial; Management Information System; Material management; Public sector; CNPQ::CIENCIAS SOCIAIS APLICADAS